Nondiffractive wavefront-shaping extended depth-of-focus intraocular lens: visual performance and patient-reported outcomes. Issue 2 (February 2022) - Kohnen, Thomas; Petermann, Kerstin; Böhm, Myriam; Hemkeppler, Eva; Ahmad, Wasim; Hinzelmann, Lisa; Pawlowicz, Katarzyna; Jandewerth, Tyll; Lwowski, Christoph
Abstract : This new nondiffractive EDoF IOL presents significantly less optical phenomena than other EDoF or mIOLs and provides good far and intermediate VA and functional near VA with high spectacle independence. Abstract : Purpose: To evaluate visual performance and patient-reported outcomes after bilateral implantation of a new nondiffractive wavefront-shaping extended depth-of-focus (EDoF) intraocular lens (IOL). Setting: Department of Ophthalmology, Goethe University, Frankfurt, Germany. Design: Prospective, single-arm, single-center study. Methods: Patient population: 16 patients (32 eyes) who received bilateral implantation of a nondiffractive wavefront-shaping EDoF IOL (AcrySof IQ Vivity) were included. Target refraction in both eyes was emmetropia. Observation procedure: Monocular and binocular uncorrected (UCVA) and distance-corrected (DCVA) visual acuity (VA), refractive outcome, defocus curve, and contrast sensitivity (CS) were evaluated 3 months after surgery with a questionnaire on optical phenomena and spectacle independence. Main outcome measure: 3-month postoperative monocular and binocular UCVA and CDVA (logMAR), defocus curve, CS, and quality of vision (QoV) questionnaire results. Results: 16 patients with 32 eyes were included. Mean spherical equivalent was −0.16 ± 0.37 diopters (D) 3 months postoperatively. Binocular uncorrected distance VA at distance, intermediate, and near was 0.01 ± 0.05 logMAR at 4 m, 0.05 ± 0.05 logMAR at 80 cm, 0.07 ± 0.06 logMAR at 66 cm, and 0.25 ± 0.11 logMAR at 40 cm, respectively. Despite some minor optical phenomena, 88% of patients would choose the same lens. 63% of patients reported no optical phenomena at all. CS was 1.25 ± 0.41 logCS (photopic), 0.96 ± 0.24 logCS (mesopic), and 0.93 ± 0.24 (mesopic + glare). Conclusions: This nondiffractive wavefront-shaping EDoF IOL provides good VA at far and intermediate distance and functional near VA. It showed good QoV and CS and high spectacle independence for distance and intermediate vision with significantly less optical phenomena than with other EDoF or multifocal IOLs.